Epoxy shaiyr zhane modifiers cospalar negіzіnde polymer cementtі compositional аndiru - Kairbaev, Бағдат (Рroblems of engineering and professional education, 2023)
. The author focuses on the production of polymer-cement compositions from epoxy resins and modifiers. The characteristic features of polymer-mineral binders are singled out and described. In conclusion, it is revealed, as far as the material in the construction industry is concerned.